Factors Associated with Anemia in Breastfeeding Mothers: A Narrative Systematic Review - Rahmiwati, Anita; Kartika Sari, Devy (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Anemia among breastfeeding women has the potential to reduce both the volume and nutritional quality of breast milk. This systematic narrative review aimed to explore and summarize the determinants related to anemia in lactating mothers. The review was conducted in accordance with PRISMA guidelines. Literature searches were carried out through PubMed and Google Scholar between March 10 and 12, 2024, using the keywords “associated factors”, “anemia”, and “lactating or breastfeeding mothers.” A total of 8,215 studies were initially identified, and seven met the final inclusion criteria. Reported prevalence of anemia among lactating women ranged from 28% to 63%. Major contributing factors included older maternal age, absence of iron supplementation during the lactation period, inadequate antenatal care visits, lower educational attainment, and limited household economic resources.